2004
DOI: 10.1037/1064-1297.12.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol and Expectancies on HIV-Related Risk Perception and Behavioral Skills in Heterosexual Women.

Abstract: This experiment tested the effects of alcohol and expectancies on determinants of safer sex according to the Information-Motivation-Behavioral Skills model. Sixty heterosexual women attended two sessions. During session 1, participants completed a set of descriptive measures; during session 2 they were randomly assigned to one of four beverage conditions: control, alcohol/low (.35 gm alcohol/kg. body weight), alcohol/moderate (.70 gm alcohol/kg. body weight), or placebo. After beverage consumption, all partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 30 publications
8
108
2
2
Order By: Relevance
“…Consistent with the Maisto et al (2004) finding, only the higher dosage increased risk-taking beyond the control condition. When intoxication and self-reported sexual arousal were examined simultaneously, alcohol had no direct impact on risky sexual behavior likelihood.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with the Maisto et al (2004) finding, only the higher dosage increased risk-taking beyond the control condition. When intoxication and self-reported sexual arousal were examined simultaneously, alcohol had no direct impact on risky sexual behavior likelihood.…”
Section: Discussionsupporting
confidence: 76%
“…Maisto et al (2002) found that women who reported a greater perceived level of intoxication also exhibited poorer condom negotiation skills in a role-playing scenario. This fi nding was replicated in a subsequent experiment (Maisto et al, 2004a). In a similar study with men, alcohol consumption itself, rather than perceived intoxication, was predictive of men's condom negotiation skill level (Maisto et al, 2004b).…”
Section: Alcohol's Effects On Sexual Risk Takingsupporting
confidence: 61%
“…However, it is concerning because greater alcohol use and intoxication are associated with impaired decision-making processes and a narrowing of one's attention that may decrease the perception of risk associated with a sexual situation (Fromme et al, 1999;Maisto et al, 2004;Steele and Josephs, 1990;Taylor and Leonard, 1983). Indeed, recent experimental research has demonstrated a link between acute alcohol intoxication and sexual appraisals among women asked to project themselves into a story depicting a sexual interaction.…”
Section: Discussionmentioning
confidence: 99%